Promoting a multi-cultural education program in private colleges in Malaysia: a personal view - Lim, Ho Peng (INTI University College, 2007)
The private education industry in Malaysia is playing a very significant role in the development of human resources, in line with the goals stated in Vision 2020. Private education institutions have mushroomed and proliferated throughout the country. Most of these private institutions provide courses catering to internationally recognized professional, technical, and academic qualifications. Since many of the courses offered are foreign-based, the significance to Malaysia is in the savings in the outflow of Malaysian currency. Most of the students attending private colleges in Malaysia, particularly in those institutions in the Klang Valley, are bilinguals. The Malaysian students and their other foreign college mates form the multiracial and multi-cultural set-up that can be harnessed and, with proper planning, can become a significant source of human development and national unity.